Does resisted & assisted freestyle swimming adversely affect stroke mechanics? Recent.evidence - Williams, B.; Sinclair, P.; Galloway, M. (coachesinfo.com)
A three-dimensional video analysis was conducted on the stroke mechanics of four female junior elite swimmers. They swam one 50m freestyle trial for each of three conditions: resisted, assisted, and free swimming. Stroke length (SL), stroke rate (SR), maximum hand depth (max hand depth), body roll, and average forward velocity (avg fwd v) were all evaluated. There was a significant difference (p < 0.05) found between conditions among SL, SR, max hand depth, and avg fwd v. During the resist trial, SL, SR, max hand depth, and avg fwd v all decreased. During the assist trial, SL, SR, avg fwd v increased, and max hand depth decreased. The changes due to resisted swimming suggest an undesirable affect on stroke mechanics, and, while some changes seen in assisted swimming may appear beneficial, both methods of tethered training remain questionable.